IMPLEMENTASI POLA DESAIN UNTUK PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN - Jason Pratama Sunarji; Mohammad Fajar; Junaedy (STMIK KHARISMA Makassar, 2019)
The aims of this study are to apply design patterns for developing library information system and analyze them from re-usability aspect. The applied design pattern consists of Factory Patterns and Façade Patterns. Factory Patterns are used to separate the process of making objects from other purchased objects. The Façade Patterns are used to reduce connectivity among classes and the complexity of the system being built. To evaluate the patterns, object-oriented metrics were used, both system that do not apply the design pattern and the proposed system (system that apply the design pattern). The results of the Object Oriented Metrics analysis using the Coupling Between Object parameter showed the decrease of the connectivity among classes so that the system is easy to reuse, in which the parameter Response for a Class (RFC) showed the reduction of the method in the class on a system that applied the design pattern which made it easier to be understood and tested. In addition, using the parameter Line of Code (LoC) showed the reduction of 228 lines code of program, from 4410 to 4182 so that the system made the program size smaller and the library information system become easier to be maintained, reused, and understood.